DUKUNGAN EMOSIONAL KELUARGA DENGAN TINGKAT KECEMASAN PADA PASIEN TUBERKULOSIS (TB) PARU - Atiek Murharyati; Lisa Rusmilah; Maula Solikhah; Erinda Pratiwi (Poltekkes Kemenkes Medan, 2021)
Tuberculosis (TB) is an infectious disease, most of which is caused by Mycobacterium tuberculosis. The psychological effect that is often experienced by TB patients is anxiety. There factors that cause anxiety, predisposition and precipitation. One of the factors that influence someone in dealing with anxiety is family support. Especially in emotional support, which can promote feelings of comfort and emotional control in TB patients. The purpose of this study was to determine the relationship between family emotional support and anxiety levels in pulmonary tuberculosis (TB) patients. This research was conducted in the Wonogiri District area. The research design used cross-sectional. The total sampling was (n = 59) in TB patients who are undergoing treatment. The research tool uses a questionnaire. Data analysis used Chi Square Test. Date were retrieved by questionnaire then analyzed using chi square with degree of meaning ?<0.05. Result and analyze, obtained p value 0.034 (p-value 0.034 <? (0.05), it means that Ho is rejected and Ha is accepted. The results a relationship between family emotional support and the anxiety level of pulmonary tuberculosis (TB) patients in Wonogiri District. And TB patients with less family emotional support are at risk of having a high level of anxiety 9.5, compared to good family support (OR: 1.909- 2,346). Suggestions for further researcher to research recommends empowering family in providing emotional support to help TB patient in emotional mastery, so as not to experience an increase in anxiety levels